The construction and health and safety management in Brazil and Portugal: a look at the small construction works - Gomes, H., (2016)
The construction industry sector has some peculiarities when comparing to other economic sectors, whether in Portugal or Brazil, it plays a key-role in developing countries. However, it is also one of the economic sectors where more work accidents occur and therefore, the industrial sector where the risk of accidents is higher. Because of this, both Brazil and Portugal have sought to improve management tools used in this sector in order to minimize the adverse effects of work accidents in this activity. The current work, , bibliographic database, aims to analyse the main management tools that are used either in Portugal or Brazil, regarding occupational health and safety conditions in small construction works, with the objective to identify future contributions. From the obtained results, it is possible to conclude that there is still much to deepen and discuss on this subject, particularly regarding the small-scale construction works. It was also possible to consolidate the idea that a knowledge and experience exchange and transfer between both countries can be important at aiming an improvement of the management tools used in this particular economic sector.